Muscle MRI of classic infantile pompe patients: Fatty substitution and edema‐like changes. Issue 6 (9th February 2017) - Pichiecchio, Anna; Rossi, Marta; Cinnante, Claudia; Colafati, Giovanna Stefania; De Icco, Roberto; Parini, Rossella; Menni, Francesca; Furlan, Francesca; Burlina, Alberto; Sacchini, Michele; Donati, Maria Alice; Fecarotta, Simona; et al.
ABSTRACT: Introduction: The aim of this study was to evaluate the muscle MRI pattern of 9 patients (median age: 6.5 ± 2.74 years) affected by classic infantile‐onset Pompe disease who were treated with enzyme replacement therapy. Methods: We performed and qualitatively scored T1‐weighted (T1‐w) sequences of the facial, shoulder girdle, paravertebral, and lower limb muscles and short‐tau inversion recovery (STIR) sequences of the lower limbs using the Mercuri and Morrow scales, respectively. Results: On T1‐w images, mild (grade 1) or moderate (grade 2) involvement was found in the tongue in 6 of 6 patients and in the adductor magnus muscle in 6 of 9. STIR hyperintensity was detected in all areas examined and was categorized as limited to mild in 5 of 8 patients. Conclusions: On T1‐w sequences, mild/moderate adipose substitution in the adductor magnus and tongue muscles was documented. STIR edema‐like alterations of thigh and calf muscles are novel findings. Correlations with biopsy findings and clinical parameters are needed to fully understand these findings. Muscle Nerve 55 : 841–848, 2017